STRATEGI KOMUNIKASI PEMASARAN PRODUK UMKM BASRENG ENDUL DALAM MENCIPTAKAN BRAND AWARNESS - Hagi Julio Salas; Fajar Junaedi; Suci Ria Ardinata (Komsospol, 2023)
The product marketing communication strategy to create Brand Awareness in UMKM (Micro, Small, Medium Enterprises) is formed from the growth of consumer interest in the snacks being sold, flavor variants in food products, as well as the potential for developing UMKM in facing increasingly fierce market competition. Of course, this cannot be separated from the marketing communications strategy that must be carried out to overcome competition. This research aims to determine the marketing communication strategy for Basreng Endul UMKM products in creating Brand Awareness. This type of research is qualitative descriptive research, by collecting data through interviews, observations and literature studies which aim to analyze and explain descriptively, namely describing to explain an object and phenomenon which will be expressed in writing and sentences. Based on the results of research conducted in the field, it can be concluded that the marketing communication strategy carried out by UMKM for Endul basreng products is to carry out points in the marketing communication mix with a focus on direct marketing through social media (Direct Marketing), word of mouth promotion. mouth or go directly into the field to offer or recommend products to consumers (Personal Selling), create attractive promotional pamphlets to introduce products (Advertising). Visual communication and recommendations are factors that influence the creation of brand awareness. This strategy is used in marketing Basreng Endul UMKM products in creating Brand Awareness.